The Chebyshev expansion based passive model for distributed interconnect networks - Wang, Janet M.; Kuh, Ernest S.; Yu, Qingjian (1999 IEEE/ACM International Conference on Computer-Aided Design : digest of technical papers : November 7-11, 1999, San Jose, California, 1999)
A new Chebyshev expansion based model for distributed interconnect networks is presented in this paper. Unlike the moment methods, this new model is optimal and it does not require the knowledge of expansion points. An automatic order selection scheme is also included in the new model. By using the integrated congruence transform, we guarantee the passivity of the new model for distributed interconnect networks. Because of the orthogonality of Chebyshev polynomials, the Modified Gram-Schmidt algorithm can be simplified. In the experimental examples, the new model is found to be accurate and efficient.